METTL7B Is Required for Cancer Cell Proliferation and Tumorigenesis in Non-Small Cell Lung Cancer - Liu, Dongcheng; Li, Wei; Zhong, Fuhua; Yin, Jianhua; Zhou, Wei; Li, Shixuan; Sun, Xuefeng; Xu, Jing; Li, Guofeng; Wen, Yuxin; Wang, Jiaqing; Hong, Malin; et al. (Frontiers in Pharmacology, 2020)
Lung cancer remains a leading cause of cancer-associated mortality worldwide, however, molecular mechanisms underlying lung cancer tumorigenesis and progression remain unknown. Here, we report evidence showing that one member of the mammalian methyltransferase-like family (METTL), METTL7B, is a potential molecular target for treatment of non-small cell lung cancer (NSCLC). METTL7B expression was elevated in the majority of NSCLC comparing to normal tissues. Increased expression of METTL7B contributed to advanced stages of tumor development and poor survival in NSCLC patients. Lentivirus-mediated shRNA silencing of METTL7B suppressed proliferation and tumorigenesis of cancer cells in vitro and in vivo. Investigation on gene expression profiles of NSCLC cells revealed that abundant cell cycle related genes were downregulated in the absence of METTL7B. Pathway enrichment analysis indicated that METTL7B participated in cell cycle regulation. Notably, CCND1, a key regulator for G1/S transition, was significantly decreased with the depletion of METTL7B, resulting in G0/G1 arrest, indicating that METTL7B is critical for cell cycle progression. Taken together, our findings implicate that METTL7B is essential for NSCLC development and progression. METTL7B might serve as a potential therapeutic target for NSCLC.